Edible coatings minimize fat uptake in deep fat fried products: A review. (October 2017) - Kurek, Mia; Ščetar, Mario; Galić, Kata
Abstract: In the past decades, edible coatings are successful used as a tool to reduce the fat uptake in deep fat fried food products. Significant interests is captured by the scientific society and the food industry sector in order to find the adequate formulation design, film forming polymer properties, components to improve adhesion and active properties. Hydrocolloid coatings can reduce the excessive oil uptake due to their interesting thermogelling properties and at the same time they are invisible and have no negative influence on the sensory attributes of fried foodstuff. Even more, fried products have low fat content with improved nutritional values, higher crispiness and better palatability. This article emphasizes the importance of adequate formulation design for a given product and its action mechanism. Different edible coating materials and their effectiveness on fried food are reviewed. Food items, such as potatoes, meat, fruit and vegetables are covered. Synergistic action with other pre-treatment technologies is also described. It is to expect that edible oil barrier coatings will become an essential strategy for launching healthier fried products and therefore they might be interesting for increasing the profit margins for snack industry. Graphical abstract: Highlights: Edible coatings can reduce the excessive oil uptake in deep fat fried food. Edible oil barriers are invisible with no negative influence on sensory attributes. Coatings are successfully used as oil barriers during frying meat and fruits. Oil barrier coatings will become an essential strategy for launching healthier fried products.